Activation of Piezo1 or TRPV2 channels inhibits human ureteral contractions via NO release from the mucosa - Liu, Jianing; Wang, Cong; Wang, Wenyu; Ding, Ning; Liu, Jiaxin; Liu, Hanwen; Wen, Jiliang; Sun, Wendong; Zu, Shulu; Zhang, Xiulin; Yan, Jieke (Frontiers in Pharmacology, 2024)
We aimed to investigate the expression and motor modulatory roles of several mechano-sensitive channels (MSCs) in human ureter. Human proximal ureters were obtained from eighty patients subjected to nephrectomy. Expression of MSCs at mRNA, protein and functional levels were examined. Contractions of longitudinal ureter strips were recorded in organ bath. A fluorescent probe Diaminofluoresceins was used to measure nitric oxide (NO). RT-PCR analyses revealed predominant expression of Piezo1 and TRPV2 mRNA in intact ureter and mucosa. Immunofluorescence assays indicate proteins of MSCs (Piezo1/ Piezo2, TRPV2 and TRPV4) were mainly distributed in the urothelium. Ca2+ imaging confirmed functional expression of TRPV2, TRPV4 and Piezo1 in cultured urothelial cells. Specific agonists of Piezo1 (Yoda1, 3–300 μM) and TRPV2 (cannabidiol, 3–300 μM) attenuated the frequency of ureteral contractions in a dose-dependent manner while the TRPV4 agonist GSK1016790A (100 nM–1 μM) exerted no effect. The inhibitory effects of Piezo1 and TRPV2 agonists were significantly blocked by the selective antagonists (Dooku 1 for Piezo1, Tranilast for TRPV2), removal of the mucosa, and pretreatment with NO synthase inhibitor L-NAME (10 μM). Yoda1(30 μM) and cannabidiol (50 μM) increased production of NO in cultured urothelial cells. Our results suggest that activation of Piezo1 or TRPV2 evokes NO production and release from mucosa that may mediate mechanical stimulus-induced reduction of ureter contractions. Our findings support the idea that targeting Piezo1 and TRPV2 channels may be a promising pharmacological strategy for ureter stone passage or colic pain relief.